Expression of Benign and Malignant Thyroid Tissue in Ovarian Teratomas and the Importance of Multimodal Management as Illustrated by a BRAF-Positive Follicular Variant of Papillary Thyroid Cancer - Wolff, Erin F. (Mary Ann Liebert, Inc., 2010)
BACKGROUND: The most common type of ovarian germ cell tumor is the teratoma. Thyroid tissue, both benign and malignant, may be a component of an ovarian teratoma. Here we review this topic and illustrate major features by presenting multimodal management of a patient with BRAF-positive disseminated follicular thyroid cancer arising in an ovarian teratoma. SUMMARY: Malignant thyroid tissue is often difficult to distinguish from benign thyroid tissue arising in ovarian teratomas. Preoperatively, an elevated thyroglobulin (Tg) level, laboratory or clinical evidence of hyperthyroidism, or ultrasonography appearance of “struma pearl” should prompt referral to oncologist for surgical management of a possibly malignant ovarian teratoma. Postoperatively, tumor tissue should be referred to pathologists experienced with differentiating benign from malignant struma ovarii. Once diagnosed, treatment of this rare condition should be handled by a team of specialists with combined treatment modalities. We cared for woman with disseminated thyroid cancer arising in an ovarian teratoma whose history illustrates the complexity of managing ovarian teratomas with malignant thyroid tissue. At age 33 she had an intraoperative rupture of an ovarian cyst, thought to be struma ovarii. During her next pregnancy, pelvic masses were noted; biopsies revealed well-differentiated papillary thyroid carcinoma, follicular variant. She was euthyroid, but had elevated serum Tg levels. Surgical staging demonstrated widely metastatic intraabdominal dissemination. A thyroidectomy revealed no malignancy. A post-(131)I treatment scan revealed diffuse uptake throughout the abdomen. She then developed abdominal pain and, on computed tomography, was found to have multiple intraabdominal foci of disease. Serum Tg was 264 ng/mL while on L-thyroxine for hypothyroidism and to obtain thyrotropin suppression. A 18 fluorodeoxyglucose positron emission tomography scan showed no pathological uptake. The tumor was found to be BRAF mutation positive (K601E). She underwent extensive secondary debulking and a second course of (131)I with lithium pretreatment. Posttreatment scan revealed diffuse abdominal uptake. Six months posttherapy, the patient is asymptomatic with a serum Tg of 18.1 ng/mL. CONCLUSIONS: Aggressive multimodal management appears to be the most promising approach for malignant thyroid tissue arising in ovarian teratomas.